2016
DOI: 10.18553/jmcp.2016.22.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Pharmacy Specialists on the Design and Implementation of a Quality Improvement Initiative to Decrease Inappropriate Medications in a Veterans Affairs Emergency Department

Abstract: This QI project resulted in a meaningful decrease in PIM prescribing in older ED adults. CPS contributions to QI can extend beyond pharmacotherapy and provider education to also include information technology tools using formulary management expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
1
21
0
2
Order By: Relevance
“…Our study highlights and confirms the findings of previous studies[5] that for the optimal drug therapy in elderly patients it is desirable to enhance and systematize the collaboration between a clinical pharmacist-geriatrician team and the treating physicians in medical units.…”
supporting
confidence: 89%
“…Our study highlights and confirms the findings of previous studies[5] that for the optimal drug therapy in elderly patients it is desirable to enhance and systematize the collaboration between a clinical pharmacist-geriatrician team and the treating physicians in medical units.…”
supporting
confidence: 89%
“…Various publications have demonstrated the importance of adopting approaches to care that will decrease the risk of adverse drug reactions for patients being treated in institutional settings. [24][25][26] One prior study of inpatients receiving treatment with insulin for hyperkalemia found an association between low pretreatment blood glucose and the risk of developing posttreatment hypoglycemia. 13 The current study also found that posttreatment hypoglycemic patients had significantly lower baseline blood glucose levels compared to those with normal posttreatment blood glucose levels; however, there were no significant differences in the dose of insulin each group received.…”
Section: Discussionmentioning
confidence: 99%
“…For research that is being conducted within pharmacy, three main types of studies seem to exist with focus on outcomes or processes at the clinical intervention or programmatic level: 1) studies of implementation of interventions within educational, community or clinical practice settings, 3,4 2) studies that apply frameworks into practice, 5,6 and 3) program assessment studies. 7,8 Program assessment studies in particular have the potential to influence health and reimbursement policies in support of practice transformation. The committee was able to identify research studies in both community pharmacy and clinical pharmacy practice settings, with a larger subset of papers dedicated to studies in the community setting.…”
Section: Literature and Funding Landscape Search Resultsmentioning
confidence: 99%